PENGARUH METODE PEMBELAJARAN GROUP INVESTIGATION DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN DASAR-DASAR DESAIN KOMUNIKASI VISUAL KELAS X DKV DI SMKN 4 PADANG - Rani Septiani; Bernediv Nurdin; Rini Novita (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This research aims to determine the influence of the Group Investigation learning method, determine student learning motivation, and the influence of the Group Investigation learning method and learning motivation on learning outcomes in the Basics of Visual Communication Design Subject Class X DKV at SMKN 4 Padang. To achieve this goal, researchers used a quantitative approach method with a Quasi Experimental research type. The total population of this study was 75 students, with details of 39 students in the control class and 36 in the experimental class. The results of the research conducted by the researcher are as follows: The average learning outcome of control class students was 62.36 and the average learning outcome of experimental class students was 86.39, which means the average learning outcome in the experimental class was higher than the control class. Based on the results of the analysis test, the results of the Group Investigation learning method showed that the learning outcomes had a sig. 0.014 < 0.05, which means there is an influence between the Group Investigation learning method on learning outcomes. Then the results of learning motivation on learning outcomes show a sig value. 0.029 < 0.05, which means there is an influence between learning motivation and learning outcomes. Finally, the results of the Group Investigation learning method and learning motivation on learning outcomes have a sig value. 0.002 < 0.05, which means there is an influence between the Group Investigation learning method and learning motivation on learning outcomes.